Ethiopian Indigenous Traditional Fermented Beverage: The Role of the Microorganisms toward Nutritional and Safety Value of Fermented Beverage - Niguse Hotessa; Jedala Robe (International Journal of Microbiology)
Ethiopia is one of the countries where a wide variety of traditional fermented beverages are produced and consumed for a long time. Traditional fermented beverages are those which are indigenous to a particular area and have been developed by the people using age-old techniques from locally available raw materials. Some of Ethiopian indigenous traditional fermented beverages products are Cheka, Keribo, Borde, Areki, Tella, Shamita, Booka, and Korefe, in which fermentation is natural and involves mixed cultures of microbes. The most common fermenting microorganisms, lactic acid bacteria and yeast, are used as probiotics, for improvement of organoleptic properties, for provision of nutritional quality and biopreservative. The nature of beverage preparation in Ethiopia, traditional household processing, associated microorganisms with a fermented beverage, and their contribution toward improving the nutritional value and safety, the extent, and its prospect in supporting the livelihood of people in Ethiopia need concern. Therefore, in the future, to improve its quality, it is important to standardize the methods of beverage fermentation processes.